Pengaruh Likuiditas, Leverage dan Profitabilitas terhadap Financial Distres dengan Ukuran Perusahaan sebagai Varibel Pemoderasi pada Perusahaan Industri dasar dan Kimia yang terdaftar di Bursa Efek Indonesia pada Tahun 2014-2019 - Fahri Muhayat; Muhammad Arief; Mhd Karya Satya Azhar (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the effect of liquidity, leverage and profitability on financial distress in basic and chemical industrial companies listed on the Indonesia Stock Exchange for the period 2014–2019. The sample in this study were basic and chemical industrial companies listed on the Indonesian Stock Exchange in 2014-2019 using purposive sampling. The data analysis technique used moderated regression analysis.The results of this study indicate that Liquidity, Leverage and Profitability have a significant effect on Financial Distress in basic and chemical industrial companies listed on the IDX for the period 2014 – 2019. Company size can moderate the effect of Liquidity on Financial Distress, but cannot moderate Leverage and Profitability on Financial Distress. in basic and chemical industrial companies listed on the IDX for the period 2014 – 2019.